Metal-free, acid-catalyzed 1,6-conjugate addition of NH-sulfoximines to para-quinone methides: accessing to diarylmethine imino sulfanone - More, Satish G.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2021)
We have reported an efficient and metal-free method for the construction of alpha-diarylmethine imino sulfanone using acid-catalyzed 1,6-conjugate addition of sulfoximines on para-quinine methides (p-QMs). This method showed broad functional group tolerance and a wide range of substrate scope with good to excellent yield. The excellent protocol exhibits mild reaction conditions with high atom economy. The practicability of the present method was supported by a Gram-scale reaction.